Characterization and Antibacterial Activity of Biosynthesized Silver Nanoparticles Using the Ethanolic Extract of Pelargonium sidoides DC. (28th December 2019) - Kgatshe, Mogomotsi; Aremu, Oluwole S.; Katata-Seru, Lebogang; Gopane, Ramokone
Abstract : Development of cost-effective and eco-friendly methods of nanoparticle synthesis could play a crucial role in integrating nanotechnology and phytomedicine for biological applications. In this study, biogenic silver nanoparticles (AgNPs) were synthesized using the ethanolic extract of Pelargonium sidoides DC at 60°C. Formation of nanoparticles was monitored using UV-Visible spectroscopy at different time intervals. A maximum absorption at 456 nm was observed as the reaction time increased, resulting in a red shift of the surface plasmon band (SPB). Attenuated total reflectance Fourier transform infrared spectroscopy (FTIR) revealed the reducing and stabilizing activity of flavonoids, coumarins, tannins, and phenols. Size and morphology of the AgNPs were analysed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM) which indicated the spherical nature of the nanoparticles with sizes ranging from 11 to 90 nm. Further characterization of the AgNPs was carried out using EDS, XRD, and Raman spectroscopy, respectively. Additionally, the AgNPs had a marginally higher antimicrobial activity when compared to the plant extract against Gram-positive Streptococcus pneumoniae (ATCC 27336) and Bacillus cereus (ATCC 10876) and Gram-negative Moraxella catarrhalis (ATCC 25240), Escherichia coli (ATCC 25922), and Pseudomonas aeruginosa (ATCC 27853).